Analisis Pengaruh Program Makan Gratis Terhadap Efektivitas Waktu Belajar Peserta Didik Di UPT SPF SD INPRES UNGGULAN TODDOPULI - Reski safira; Devi Reskiawaliyah Wahyuni; A.Muhajir Nasir; Dian Ekawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Free Nutritious Meal Program (MBG) on the effectiveness of students’ learning time at UPT SPF SD Inpres Unggulan Toddopuli. The research employed a quantitative approach with an ex post facto design. Data were collected through questionnaires and analyzed using validity tests, reliability tests, and simple linear regression. The findings revealed that the Free Nutritious Meal Program has a positive and significant influence on students’ learning time effectiveness, with a Significance F value of 0.001 < 0.05 and a regression coefficient of 0.499. This indicates that better implementation of the meal program contributes to improved learning time effectiveness. However, the program requires approximately 15–20 minutes of daily implementation, resulting in reduced instructional time. Despite this, the program provides substantial benefits to students’ physical readiness, focus, and engagement in learning. The study recommends optimizing time management and conducting regular evaluations to ensure that the program continues to support learning quality without reducing essential instructional hours.